Culture Shock and Coping Mechanisms of International Korean Students: A Qualitative Study - Kent D. McLeod; Zohreh R. Eslami; Keith M. Graham (Cranmore Publishing, 2021)
International students bring academic, cultural, and economic value to universities around the world. However, adjustments for these students can be difficult as a result of culture shock, resulting in early exit from the university. In order to help inform university personnel on how to better assist international students, this study examines the interpersonal, psychological, and physiological symptoms of culture shock of three Korean international graduate students at a large public university in the southwest United States. Data were collected through three interviews and seven weekly online journals. The findings uncovered the existence of culture shock for each of the three participants to differing degrees at various times throughout the semester. In particular, a comparatively higher incidence of interpersonal and psychological culture shock symptoms compared with physiological ones was displayed, thus showing strong support for theories that conceptualize culture shock as individualized in nature. In addition, the data revealed that personal characteristics, family, religion, and exercise all played a role in the participants' abilities to cope with culture shock. The results of this study could help universities better understand and support international students, ensuring that the university can benefit from the unique value these students bring to campus.